SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) INTERVENTION FOR PREOPERATIVE ANXIETY: A LITERATURE REVIEW - Kaslinda Nur Umifa (JTH: Journal of Technology and Health, 2026)
Anxiety is an emotional response that often occurs in patients who are about to undergo a procedure or surgery. Pre-operative anxiety not only impacts the patient's psychology, but also affects the patient's physiological condition. Non-pharmacological therapy is a safer option in handling pre-operative anxiety, one of the interventions that can be given is Spiritual Emotional Freedom Techniques (SEFT). The aim of the study is to identify and gain a better understanding of the benefits of implementing the Spiritual Emotional Freedom Technique (SEFT) intervention in overcoming pre-operative anxiety. This article's research method used a literature review study method. Articles were searched from several databases including Science Direct, PubMed, and Google Scholar. This study used inclusion criteria such as the research focus on Spiritual Emotional Freedom Technique (Seft), and articles from the last 5 years, from 2022 to 2026. Exclusion criteria were articles published before 2022, duplicate articles, and incomplete articles. The results of seven articles reviewed consistently show that the SEFT intervention is beneficial in reducing preoperative anxiety in patients through a combination of spiritual affirmations, self-acceptance, relaxation, and tapping on specific points on the body. This can improve psychological readiness, reduce emotional tension, and support patient readiness for preoperative procedures. The conclusion, intervention of SEFT may be beneficial for various patients experiencing anxiety, especially patients who are about to undergo surgery.